STRATEGIA PROMOCJI MIASTA NA PRZYKŁADZIE WAŁBRZYCHA - Kamil Glinka (In Gremium. Studies in History, Culture and Politics, 2012)
TOWN PROMOTION STRATEGY. THE CASE OF WAŁBRZYCHThe main aim of this article is to present the formal and legal foundations of the promotion of Wałbrzych. Therefore, it outlines the assumptions of the most important documents of strategic character which refer to promotional actions. The author also aims at confirming the thesis that over the past few years Wałbrzych has been undergoing a gradual professionalization in terms of creating such documents and the assumptions found on their pages. Such an analysis has to include a glossary and be complemented with a brief characteristic of Wałbrzych in order to present its specificity. This is important, especially when taking into account the way the town is perceived by the public opinion on one hand and the need to outline the assumptions of documents referring to the promotion of Wałbrzych, which are to some extent created on the basis of social, political and economic reality, on the other.